Procurement Strategy for Facility Management Improvement in PT MBI Tbk - Bram Sunardi; Aries F. Firman (AIBPM Publisher, 2021)
The aims of this study are to determine the major challenges and root cause in facilities management and to recommend solutions to solve the major challenges in PT MBI, which can also be extended to other manufacturing company. The research employs qualitative method to obtain information and opinion from competent stakeholders through interview. Root cause analysis is determined by mapping the primary data obtained from the interview and extracted into keyword. This study finds there are 6 major challenges and root causes causing the issues in facility management, which are communication and close coordination gap, multiple vendors, unprofessional vendor, poor experience development and training, no SLA and report standardization, and complex scope and activity. The result of this study indicates that PT MBI should conduct tender to implement total facilities management (TFM), create more stringent vendor selection criteria, experienced personnel and regular training, involve users to create SLA, KPI, and report, setup regular meeting structure, and review internal SOD and create proper contractual agreement. The implication of the result indicates the importance of internal processes to trigger facilities management and operation improvement in a company.